Visualizing the 'invisible' - Moriarty, Philip (MIT Press Journals, 2015)
The ability of scientists to image and manipulate matter at the (sub)atomic scale is a result of stunning advances in microscopy. Foremost amongst these was the invention of the scanning probe microscope, which, despite its classification as a microscope, does not rely on optics to generate images. Instead, images are produced via the interaction of an atomically sharp probe with a surface. Here the author considers to what extent those images represent an accurate picture of ‘reality’ at a size regime where quantum physics holds sway, and where the image data can be acquired and manipulated in a variety of ways.